DIFFERENCES IN THE MOTORIC ABILITIES OF STUDENTS DUE TO THE BODY MASS INDEX (BMI) - Arben Osmani; Mamaj Driton (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2014)
Introduction:The research has been conducted in order to establish differences in motoric abilities due to the body mass index (BMI) with the tested students at the eighth grade (Barlow, & the Expert Committee, 2007). Methods: During the research 160 male students aged 14 were tested. On the base of (BMI) they were divided into 3 groups (normal, overweight, and with obesity). They were tested with 6 motor tests for: explosive power, repetitive power, coordination, equilibrium, precision, and flexibility. Along with basic statistic parameters, the differences between the groups are established through: ANOVA, MANOVA and LSD-tests. Results: The obtained results are presented in 5 tables. On the base of the results, a statistically significant difference in favor of the group of normal body mass index is recorded in the following tests: standing a long jump, agility on the ground and keeping balance on one leg. Discussion: The results obtained in this research indicate that obesity and overweight cause a negative effect and result in lower performances concerning some motoric abilities. On the base of the obtained results, it is concluded that the group of students of normal body mass index achieved the best results in the motoric abilities with assessing the following: explosive power, coordination, and equilibrium. As for the motoric ability concerning: precision, repetitive power, and flexibility, there are no established statistically significant differences between the three groups. The obtained results correspond with some former researches (Milanese, et al., 2010; Zhu, Sheng, Wu, & Cairney, 2010), and some do not (De Toia, et al., 2009). References: Barlow SE et al. (2007). Pediatrics, 120, 164-92. De Toia D, Klein D, Weber S, Wessely N, Koch B, Tokarski W, Dordel S, Strüder H, Graf C (2009). European Journal of Obesity, 2(4), 221-5. Zhu YC, Sheng K, Wu SK, Cairney J (2011). Research in Developmental Disabilities, 32(2), 801-7. Milanese C, Bortolami O, Bertucco M, Verlato G, Zancanaro C (2010) Journal of Human Sport & Exercise, 5(2), 265-79.